Cultural logics and individualism-collectivism: a conceptualization of the two frameworks from a cultural dynamical perspective - Yoshihisa Kashima; Said Shafa; Khandis Blake (Current Research in Ecological and Social Psychology)
Cultural logics of dignity, face, and honour (Leung & Cohen, 2011) have become a significant focus of research in culture and psychology. However, how they relate to the existing literature on individualism and collectivism has been left unclarified despite their apparent conceptual links. This article attempts to clarify how cultural logics relate to individualism and collectivism from a perspective of the psychology of cultural dynamics. After describing our approach to the psychology of cultural dynamics, we suggest that cultural logics and individualism-collectivism can be conceptualized as cultural ideas and practices about how to structure social organization. Honor and face logics are typically embedded in kin-based and social network-based collectivisms, respectively. In contrast, dignity logic is a particular configuration of individualism combined with a particular type of collectivism called attribute collectivism, which emphasizes social connections based on a shared attribute that defines a group membership. We then argue that the prevalence of cultural logics in a human population depends on the socio-ecological environments with which the population interacts. Honor becomes prominent under severe intergroup competition, face under a great need for intragroup cooperation, and dignity under moderate levels of intragroup cooperation and intergroup competition. In the final section, we piece together recent empirical evidence to hypothesize socio-ecological factors that have, over time, given rise to contemporary cultural diversity across Eurasia – widespread kin/clan collectivism with honor logic, but dignity in the West and face in the East.